2023
DOI: 10.1186/s12891-023-06910-z
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden, fatigue, sleep quality and perceived social support in hemodialysis patients with musculoskeletal discomfort: a single center experience from Egypt

Mohammed Kamal Nassar,
Samar Tharwat,
Sara M. Abdel-Gawad
et al.

Abstract: Background and aims Musculoskeletal disorders (MSDs) are commonly encountered in hemodialysis (HD) patients. However, the causes linked to these disorders are still partially defined. The aim of this study was to determine the frequency of MSDs and their relationship to a variety of clinico-social characteristics such as sleep quality, mood disorders, fatigue, and social support, in addition to the patients’ clinical and therapeutic profile. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…[ 20 ] Gender and ALB levels showed less consistent associations with sleep quality. One study reported that females had a higher risk of sleep disorders than males, [ 21 ] while another study found no significant gender difference in sleep quality. [ 22 ] ALB levels did not consistently show an association with sleep quality across the studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Gender and ALB levels showed less consistent associations with sleep quality. One study reported that females had a higher risk of sleep disorders than males, [ 21 ] while another study found no significant gender difference in sleep quality. [ 22 ] ALB levels did not consistently show an association with sleep quality across the studies.…”
Section: Discussionmentioning
confidence: 99%